Fetal Stem Cells in Regenerative Medicine Principles and Translational Strategies - Fauza, Dario O.; Bani, Mahmud (Stem Cell Biology and Regenerative Medicine,, 2016)
This book explores the regenerative properties of fetal stem cells, from feto-maternal cell traffic through perinatal stem cells, with a discussion of key topics including stem cell banking, drug screening, in utero stem cell transplantation and ethical considerations. The expertly authored chapters also delve into embryonic, amniotic membrane, and umbilical cord blood stem cells; fetal development models; fetal cell reprogramming; culture methods; disease models; perinatal gene therapy, and more. These chapters are grouped into four sections, each discussing a separate prenatal stem cell population and providing fascinating historical contexts for our knowledge of these systems. Featuring a foreword written by the renowned Dr. Joseph Vacanti of the Harvard Stem Cell Institute, Fetal Stem Cells in Regenerative Medicine: Principles and Translational Strategies is a welcome and timely contribution to the Stem Cell Biology and Regenerative Medicine series. It is essential reading for scientists and researchers, clinicians and residents, and advanced students involved in stem cells, regenerative medicine, tissue engineering, and related disciplines such as embryology.